Energy Conservation Behavior of Thai University Students - Kunanunt Thayayuth; Paitoon Pimdee (My University, 2018)
An estimated 1.2 billion people, or 16% of the global population, did not have access to electricity in 2015. Therefore, access and the conservation of energy have become critical issues in a country’s quest for economic prowess and sustainability. This research, therefore, aimed to study the energy-conservation behavior of university students, and compare their energy-saving behavior categorized by gender and university group. The sample of 900 undergraduate students came from 15 Thai public universities under the Office of the Higher Education Commission [OHEC] in the 2013 academic year. The sample was randomly selected using a multi-stage sampling method. The instrument used to collect data in this research was a 5-level rating-scale questionnaire with reliability which was between 0.86-0.94. Data were analyzed using mean, standard deviation, t-test for independent sample and one-way ANOVA. The findings revealed that the students exhibited energy-conservation behavior in a family context at a high level, while energy-conservation behavior for themselves, and for the public was at a moderate level. Male and female students had different energy-conservation behaviors, and students under different university groups had distinct energy-conservation behaviors.
Keywords: Sample (material); Environmental Education and Sustainability